Better survivals in adolescent and Young adults, compared to adults with acute lymphoblastic leukemia – A multicenter prospective registry in Thai population. (December 2019) - Limvorapitak, Wasithep; Owattanapanich, Weerapat; Utchariyaprasit, Eakkapol; Niparuck, Pimjai; Puavilai, Teeraya; Tantiworawit, Adisak; Rattanathammethee, Thanawat; Saengboon, Supawee; Sriswasdi, Chantarapa; Julamanee, Jakrawadee; Saelue, Piroon; Polprasert, Chantana; et al.
Highlights: Adult ALL has inferior survival compared to adolescent and young adult (AYA) group. AYA ALL group has more male, more T-phenotype and less BCR-ABL1 mutation. Allogeneic stem cell transplantation improves survival in ALL patients. Abstract: Adult acute lymphoblastic leukemia (ALL) is an uncommon hematologic malignancy with high relapse and mortality rate. This study aimed to describe characteristics and outcomes of Thai ALL patients, and to determine the differences between adolescent and young adult (AYA) and adult ALL. ALL patients aged > 15 years were prospectively enrolled from 2015 to 2017. AYA patients were defined as age ≤ 39 years. Out of the 188 enrolled ALL patients, 9 were excluded due to changes in diagnosis or incomplete data. From the remaining 179 patients, 103 (57.5%) were AYA and 76 (42.5%) were adult. AYA ALL patients were predominantly male, had higher T-cell phenotype, higher white blood cells and hemoglobin, with lower frequency of Philadelphia chromosome or BCR-ABL1 mutation. All patients received treatment by adult hematologist, however 40.8% of AYA ALL patients were treated with pediatric adapted protocol. The effects of stem cell transplantation (SCT) and age were determined by stratified patients as: AYA - no SCT 91 (51.1%), AYA - SCT 12 (6.7%), adult - no SCT 64 (36.0%) and adult - SCT 11 (6.2%). The 2-year overall survival were: 53.9%, 60.6%, 39.2% and 70.1%, respectively. The 2-year event-free survival were: 45.0%, 54.0%, 21.0% and 49.9%, respectively. This is a large multicenter ALL cohort study conducted in Thailand. Patients who underwent SCT showed significantly improved OS and EFS, confirming the benefit of graft-versus-leukemia effect in ALL. However, further studies with longer follow-up, expanded use of SCT, use of molecular data, and minimal residual disease status are warranted.